POTENSI ANTIOKSIDAN ALAMI PADA EKSTRAK DAUN JAMBLANG (Syzigium cumini (L.) Skeels) - Ayu Nirmala Sari (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2017)
Various diseases can be triggered by the condition of oxidative stress in the body. Oxidative stress is a condition that occurs in cells when free radicals are present in excess amounts. To reduce the negative effects and negative effects of these free radicals, the body needs antioxidants. The aim of this research is to know the antioxidant potential of black plum leaf extract (Syzigium cumini (L.) Skeel) using DPPH method. Based on the results of antioxidant potential testing in black plum leaf extract known that it has antioxidant content that is classified as very active with an IC 50 value of 8.85. The results of this study indicate that the leaves of black plum (Syzigium cumini (L.) Skeel have the potential to be developed as a source of natural antioxidants for humans.